History of The Establishment of Mts Al-Khairat Pinotu in Improving the Quality of Islamic Education - Nurahma, Aditia; Kapile, Charles (Kirana Publisher (KNPub), 2025)
This research aims to reveal the background of the establishment and development of Madrasah Tsanawiyah (MTS) Al-Khairat Pinotu in Piloto Village, Toribulu District, Parigi Moutong Regency, Central Sulawesi. This research uses a qualitative approach with historical (historical) methods, which includes four main stages, namely heuristic (collection of sources), source criticism, interpretation, and historiography. Data was obtained through in-depth interviews with local education figures, direct observations, and related archival documentation. The results of the study show that MTS Al-Khairat Pinotu was established in 1998 on the initiative of local community leaders in response to the need for Islamic-based junior high school education that is easily accessible to the people of Pinotu Village and its surroundings. Originally named MTS Nurul Muttahidah Pinotu, this institution then switched its auspices to the Al-Khairat Foundation in 2005 in order to be able to access official school operational assistance. The role of community leaders is very large in establishing and managing this madrasah, as well as in building the character of students through religious education and local values. This research confirms that the presence of MTS Al-Khairat Pinotu makes a significant contribution to improving the quality of Islamic education, expanding access to education in remote areas, and forming a young generation that is faithful, knowledgeable, and noble.